Human factors in aviation - Wiener, Earl L.; Nagel, David C. (Academic Press series in cognition and perception., 1988)
Since the 1950s, a number of specialized books dealing with human factors has been published, but very little in aviation. Human Factors in Aviation is the first comprehensive review of contemporary applications of human factors research to aviation. A "must" for aviation professionals, equipment and systems designers, pilots, and managers--with emphasis on definition and solution of specific problems. General areas of human cognition and perception, systems theory, and safety are approached through specific topics in aviation--behavioral analysis of pilot performance, cockpit automation, advancing display and control technology, and training methods